Human Inborn Errors of Immunity (HIEI): predominantly antibody deficiencies (PADs): if you suspect it, you can detect it - Maria Marluce dos Santos Vilela (Elsevier, 2021)
Objective: This minireview gathers the scientific foundations of the literature on genetic errors in the development of the humoral immune system to help pediatricians suspect these defects. Sources: A systemic search using the PubMed MEDLINE database was performed for all Predominantly Antibody Deficiencies (PADs) described in the 2020 IUIS Expert Committee for PID classification system, combined with terms for hypogammaglobulinemia. Search terms for PADs were based on the listed names and affected genes as classified by the IUIS 2020. Abstracts of the results were reviewed to find relevant case series, review articles of PADs associated with infection, opportunistic infection, autoimmunity, cytopenias, malignancies, inflammatory diseases, neurological and respiratory diseases. References from relevant articles were further reviewed for additional references. Relevant findings were grouped in accordance with the IUIS 2020 classification system. Clinical and genetic features, if known, were described. Data synthesis: PADs refer to impaired antibody production due to molecular defects intrinsic to B cells or a failure of interaction between B and T cells. The patients develop recurrent or chronic infection or respond to the antigens with dysregulation of the immune function, causing severe allergy, autoimmunity, inflammation, lymphoproliferation and malignancy. The diagnosis is a combined exercise of clinical and laboratory investigation similar to that performed by Bruton (1952). In the context of SARS-CoV-2 infection, the experience of XLA and CVID patients has been surprising. Variants in 39 genes were reported as causing PADs, but the clinical heterogeneity within each variant is not clear. Conclusion: Bruton (1952) used clinical expertise and protein electrophoresis to identify XLA. The IUIS (2020) committee used immunoglobulins and B lymphocyte to characterize PADs. Pediatricians should suspect it to detect it and prevent morbidities that can have an astonishing and irreversible impact on the child's life.